2001
DOI: 10.1007/bf02493021
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of furathiocarb and metabolites in biological tissues by high-performance liquid chromatography and post-column derivatization

Abstract: Key WordsColumn liquid chromatography Post-col u m n derivatization Dermal pharmacokinetics Furathiocarb, carbofuran, 3-hydroxycarbofuran and 3-ketocarbofuran SummaryA new method to determine simultaneously the amount of furathiocarb and metabohtes: carbofuran, 3-hydroxycarbofuran, and 3-ketocarbofuran in biological tissues such as liver and kidney is described. The method consists of extraction of samples with acetone, filtration, partition, purification of target analytes through a silica gel column and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…This implies that 3‐hydroxycarbofuran was excreted more rapidly in urine than carbofuran because of its high water solubility. This finding was in agreement with our earlier work with furathiocarb which showed that 3‐hydroxycarbofuran was not detected in kidney sample 24. 3‐Ketocarbofuran, another metabolite of furathiocarb, was not detected due to its hydrolytic instability, as observed in plasma 11…”
Section: Resultssupporting
confidence: 93%
“…This implies that 3‐hydroxycarbofuran was excreted more rapidly in urine than carbofuran because of its high water solubility. This finding was in agreement with our earlier work with furathiocarb which showed that 3‐hydroxycarbofuran was not detected in kidney sample 24. 3‐Ketocarbofuran, another metabolite of furathiocarb, was not detected due to its hydrolytic instability, as observed in plasma 11…”
Section: Resultssupporting
confidence: 93%
“…Carbofuran and 3-hydroxy-carbofuran were measured in liver, while only carbofuran was measured in kidney. Furathiocarb was not detected and only traces of 3-ketocarbofuran were detected at 12 h after treatment [28] .…”
Section: Resultsmentioning
confidence: 92%
“…Furathiocarb was metabolized only to the more toxic carbofuran in an in vitro dermal penetration study with rat abdominal skin using the static diffusion cell [26] . Carbofuran and 3-hydroxycarbofuran were detected in liver, while only carbofuran was detected in kidney after dermal treatment of Sprague-Dawley rats with furathiocarb [28] .…”
Section: Introductionmentioning
confidence: 94%
“…The cleavage of the N-S bond gave carbofuran (Marsden et al 1982). Furathiocarb was found to be metabolized to carbofuran and 3-hydroxycarbofuran following dermal treatment (Liu et al 2001(Liu et al , 2002. However, virtually no information is available on the dermal penetration through rat skin, which could be an important factor for the human exposure risk assessment.…”
Section: Introductionmentioning
confidence: 97%